Assessment of uranium, thorium and potassium-40 in Kelantan river basin / Siti Afiqah Abdul Rahman @ Hussin - Abdul Rahman @ Hussin, Siti Afiqah (2015)
Granitic rocks in the Kelantan State, contribute higher natural background activity than usual in environment because of it has characteristic of regions that were believed to produce significant concentrations of Naturally Occurring Radionuclides Material (NORMs) such as U and Th. Moreover, human activities such as deforestation and mineral mining in Kelantan were responsible for the NORMs mobility in the surrounding environment. Radiation from the NORMs may cause health risk to human health through the external and internal exposure. In this study, a radiological monitoring was done in the area where based on geological map of Kelantan containing uranium deposits. Soil, water and sediment were taken at 55 locations along the Kelantan river basin. As natural radionuclides that may present in the water, Water Quality Standard Malaysia introduces radium as one of the parameters that should be monitored. Radium in drinking water cannot exceed 0.1 Bq/L. Thus, 48 of aqueous samples, 25 L each, were collected along Kelantan River basin, acidify to pH 2 and filtered before the analysis. The extraction method was used to extract 222Rn in aqueous samples. Measurements of activity concentration of 222Rn were done using liquid scintillation counter (LSC) and were calculated to get the activity concentration of 226Ra. The LSC was set up to the optimum discriminator level and counting was done using alpha-beta mode. The results show that activity concentration of 226Ra range between 0.06 - 0.39 Bq/L for unfiltered samples and 0.06-0.37 Bq/L for filtered samples. The Annual Effective Dose is ranging from 13-80 jxSv/y, however are still below the WHO recommended reference level of 100 jxSv/y for river water. The radioisotopes may present in the water caused of geological erosion from the groundwater and dissolution of uranium-bearing rocks due to changing of temperature in the earth crust and also because of the erosion of the surface soils. Activity concentration of 226Ra, 228Ra and 40K and concentration of U and Th were evaluated in sediment and soil. Sediment and soil was dried, ground, sieved and then measured using Gamma Spectrometer and X-ray Fluorescence. Activity concentrations of 226Ra range between 378.1 - 579.7 Bq/kg, 228Ra 431.6 - 847.2 Bq/kg and 40K 5837.4-8421.2 Bq/kg in sediment. The calculated Hex range 4.5-6.3 and Absorbed Dose Rate is range between 690.6 -1089.9 nGy/h giving the highest exposure at Location 13.Activity concentrations of 226Ra range between 41.1 - 369.4 Bq/kg, 228Ra 49.7 - 390.6 Bq/kg and 40K 486.8 - 2362.3 Bq/kg in soil. The Hex is ranging from 0.4 to 2.9 and the Absorbed Dose Rate is ranging from 72.4-483.2 nGy/h. Concentration of U range from 1.31 - 9.41 mg/kg and concentration of Th range from 3.79 - 16.32 mg/kg. Based on the results of concentration of U and Th, prediction maps were plotted. It shows that the highest concentrations of U and Th are at the center of Kelantan state such as Jeli, Dabong and Kuala Krai. The area of Kota Bharu shows an accumulation of U and Th as river water flows from South to North. The prediction concentration of U and Th in an area of Gua Musang is lower than the other places. In conclusion, there were a significant amount of U and Th in Kelantan state.